1972
DOI: 10.1128/jb.110.3.809-817.1972
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for the Action of Oxathiin and Thiazole Derivatives on the Succinic Dehydrogenase System of Ustilago maydis Mitochondria

Abstract: The inhibitory effect of fungitoxic derivatives of 1, 4-oxathiin on substrate oxidation by the basidiomycete Ustilago maydis is diminished by a single-gene mutation (oxr). The difference between mutant and wild type is approximately the same on the basis of inhibition of either growth and operation of the tricarboxylic acid cycle in intact cells or succinate-driven reduction of ferricyanide by mitochondrial preparations. The mutation affects the behavior of the succinic dehydrogenase system of mitochondria not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…It is unclear how SDH activity was actually measured, but as carboxin inhibited the SDH activity almost completely in the wild-type membranes, SDH was probably measured with ferricyanide as the electron acceptor. A similar chromosomal mutation in U. maydis resulted in a carboxin-resistant, succinate-dependent reduction of ferricyanide or DCIP (28,29). The mutation has probably decreased the affinity of the binding site for the inhibitor.…”
Section: Downloaded Frommentioning
confidence: 99%
“…It is unclear how SDH activity was actually measured, but as carboxin inhibited the SDH activity almost completely in the wild-type membranes, SDH was probably measured with ferricyanide as the electron acceptor. A similar chromosomal mutation in U. maydis resulted in a carboxin-resistant, succinate-dependent reduction of ferricyanide or DCIP (28,29). The mutation has probably decreased the affinity of the binding site for the inhibitor.…”
Section: Downloaded Frommentioning
confidence: 99%
“…[2][3][4] Carboxamide fungicides, representing an old class of chemistry originating from the late 1960s, have been shown to inhibit succinate dehydrogenase (Sdh), an important component of the mitochondrial respiratory chain (complex II). Succinate dehydrogenase inhibitors (SDHIs) impact electron transport by blocking the quinone-binding site of Sdh formed by subunits B, C and D. [5][6][7][8] In contrast to the narrow spectrum of early-generation SDHIs, the latest generation of SDHIs have shown broad-spectrum control of Ascomycota, including Z. tritici. 9,10 Following the 2003 introduction of boscalid, the first of the new generation of SDHIs with strong eyespot activity, 9 other SDHIs, such as bixafen, fluxapyroxad, isopyrazam, penthiopyrad and benzovindiflupyr, that are very effective in controlling Septoria leaf blotch have also been registered in Europe since 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxamide fungicides, representing an old class of chemistry originating from the late 1960s, have been shown to inhibit succinate dehydrogenase (Sdh), an important component of the mitochondrial respiratory chain (complex II). Succinate dehydrogenase inhibitors (SDHIs) impact electron transport by blocking the quinone‐binding site of Sdh formed by subunits B, C and D . In contrast to the narrow spectrum of early‐generation SDHIs, the latest generation of SDHIs have shown broad‐spectrum control of Ascomycota, including Z. tritici , .…”
Section: Introductionmentioning
confidence: 99%
“…If the proposal that systemic fungicides are actively secreted from some resistant fungj is correct, then carboxin and oxycarboxin may indeed penetrate the membranes of non-basidiomycete fungj, but may then be actively secreted from the mycelia, so that no net uptake is observed. However, this explanation is less likely to apply to basidiomycete fungi (nomially susceptible to oxathiins) which have mutated to resistance; Georgopoulos, Alexandri and Chrysayi (1972) have already shown that such resistance can be due in Ustilago to a single mutation in the succinic dehydrogenase system.…”
Section: Discussionmentioning
confidence: 99%